Tackling Controversial Issues in Primary Education: Perceptions and Experiences of Student Teachers - Woolley, Richard (Religions, 2020)
This paper considers the nature and definition of controversial issues in primary education, exploring how they may be deemed controversial in different ways according to context. Drawing on research undertaken with student teachers in their final year of study at universities in England, it explores the issues that they feel apprehensive about facing in their first teaching post and those that they feel it is important to explore with children. It identifies issues relating to relationships, religion and belief and bereavement as being of significant concern, suggesting priorities for teacher training courses and contrasting these with research undertaken a decade earlier.